Mannose-specific intercellular aggregation of rat thymocytes and Escherichia coli cells triggered by temperature - Timoshenko, A.V.; Gerasimova, L.K.; Kolupaeva, L.I.; Cherenkevich, S.N. (Биополимеры и клетка, 1994)
D-mannose was shown to induce disaggregation of rat thymocytes and E. coli AB1157 cells at any stage of the process. Mannose-specific aggregation of thymocytes and E. coli was inhibited by heating as opposed to concanavalin A-induced thymocyte aggregation. The process was completely reversible at the rapid temperature changes, indicating its membrane not intracellular mechanism. Taken together, the results demonstrate that mannose-specific intercellular contacts can be affected differently by temperature.